Intracellular Ca(2+) is important for flagellin-triggered defense in Arabidopsis and involves inositol polyphosphate signaling - Ma, Yi (J Exp Bot, 2017)
Cytosolic Ca(2+) increase is a crucial and early step of plant immunity evoked by pathogen-associated molecular patterns (PAMPs) such as flagellin (flg). Components responsible for this increase are still not uncovered, although current models of plant immune signaling portray extracellular Ca(2+) influx as paramount to flg activation of defense pathways. Work presented here provides new insights into cytosolic Ca(2+) increase associated with flg-induced defense responses. We show that extracellular Ca(2+) contributes more to immune responses evoked by plant elicitor peptide (Pep3) than that evoked by flg, indicating an intracellular Ca(2+) source responsible for immune responses evoked by flg. Genetic impairment of the inositol polyphosphate (InsP) and G-protein signal associated with flg perception reduced flg-dependent immune responses. Previous work indicates that prior exposure of Arabidopsis plants to flg leads to an immune response reflected by less vigorous growth of a pathogenic microbe. We found that this immune response to flg was compromised in mutants lacking the ability to generate an InsP or G-protein signal. We conclude that the recruitment of intracellular Ca(2+) stores by flg may involve InsP and G-protein signaling. We also found a notable difference in contribution of intracellular stores of Ca(2+) to the immune signaling evoked by another PAMP, elf18 peptide, which had a very different response profile to impairment of InsP signaling. Although Ca(2+) signaling is at the core of the innate immune as well as hypersensitive response to plant pathogens, it appears that the molecular mechanisms generating the Ca(2+) signal in response to different PAMPs are different.